2014
DOI: 10.1021/es4049412
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotope Analysis of Saline Water Samples on a Cavity Ring-down Spectroscopy Instrument

Abstract: The analysis of the stable hydrogen and oxygen isotope composition of water using cavity ring-down spectroscopy (CRDS) instruments utilizing infrared absorption spectroscopy have been comprehensively tested. However, potential limitations of infrared spectroscopy for the analysis of highly saline water have not yet been evaluated. In this study, we assessed uncertainty arising from elevated salt concentrations in water analyzed on a CRDS instrument and the necessity of a correction procedure. We prepared vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 40 publications
2
47
1
1
Order By: Relevance
“…1.00565.0500) was added and the vials were capped, shaken well, and left for 1 h at 23°C for acid dissociation; (3) the vials were opened and purge/bubbled for ~10 min using ultrahigh‐purity helium in a custom‐designed manifold with 0.3 μm fused‐silica capillaries inserted to the bottom of the vials; and (4) after purging, the vials were capped and transferred to an autosampler tray. The vials used for purging are commonly used for samples analyzed using the CTC PAL autosampler with various instruments …”
Section: Resultscontrasting
confidence: 66%
“…1.00565.0500) was added and the vials were capped, shaken well, and left for 1 h at 23°C for acid dissociation; (3) the vials were opened and purge/bubbled for ~10 min using ultrahigh‐purity helium in a custom‐designed manifold with 0.3 μm fused‐silica capillaries inserted to the bottom of the vials; and (4) after purging, the vials were capped and transferred to an autosampler tray. The vials used for purging are commonly used for samples analyzed using the CTC PAL autosampler with various instruments …”
Section: Resultscontrasting
confidence: 66%
“…The CRDS‐based δ 18 O measurements of both freshwater (Benetti et al, ) and seawater (Walker et al, ) have been found to be equivalent to high‐quality measurements by isotope ratio mass spectrometry. The salt effect (Benetti et al, ) on δ 18 O and δD measurement of seawater is within the range for CRDS analytical uncertainty if the vaporizer is frequently cleaned (Skrzypek & Ford, ). The salt effect is negligible for our multiyear sea ice and snow samples due to their low salinity (<7 psu).…”
Section: Methodsmentioning
confidence: 95%
“…Raw values of δ 18 O and δ 2 H samples were normalized to the Vienna Standard Mean Ocean Water scale, based on three laboratory standards, each replicated twice and reported in per mil (‰). The long‐term analytical uncertainty (one standard deviation) was determined as 0.8‰ for δ 2 H and 0.06‰ for δ 18 O (Skrzypek & Ford, ).…”
Section: Methodsmentioning
confidence: 99%